Submerged healing following surgical treatment of periimplantitis: a case series - Ann-Marie Roos-Jansa°ker (Blackwell Synergy, 2007)
Objectives: The aim was to study a regenerative surgical treatment modality for peri-implantitis employing submerged healing. Material and Methods: Twelve patients, having a minimum of one osseointegrated implant with peri-implantitis, with a progressive loss of X3 threads (1.8 mm) following the first year of healing were involved in the study. After surgical exposure of the defect, granulomatous tissue was removed and the implant surface was treated using 3% hydrogen peroxide. The bone defects were filled with a bone substitute (Algipores), a resorbable membrane (Osseoquests) was placed over the grafted defect and a cover screw was connected to the fixture. The implant was then covered by flaps and submerged healing was allowed for 6 months. After 6 months the abutment was re-connected to the supra-structure. Results: A 1-year follow-up demonstrated clinical and radiographic improvements. Probing depth was reduced by 4.2mm and a mean defect fill of 2.3mm was obtained. Conclusion: Treatment of peri-implant defects using a bone graft substitute combined with a resorbable membrane and submerged healing results in defect fill and clinical healthier situations.